ABOUT THE ARTISTIC SKILLS OF ALISHER NAVOI - Sayliyeva Z.R. (International Journal of Literature and Language Studies, 2026)
Alisher Navoi's first collection was composed in 1478-1979. The influence of commonality, cooperation and solidarity in the creative experience of the geniuses of Mutakallim is also evident in the collection of Alisher Navoi. If it was a tradition in the classical literature of the East to start the devon with praise and ghazal, Alisher Navoi would not have considered it in the preface of "Badoe` ul-bidoya" as one of the peculiarities of his collection. According to Khamsat ul-Mutayyir, Abdurahman Jami wrote about this in the catalog of his "college".